-10 < x < 11
suy ra : x = { -9 ; -8 ; .... ; 9 ; 10 }
Vậy tổng tất cả số nguyên x là :
( -9 ) + ( -8 ) + ... + 9 + 10
= 10
Ta có:\(x\in\left\{-9;-8;-7;-6;-5;-4;-3;-2;-1;0;1;2;3;4;5;6;7;8;9;10\right\}\)
-9+-8+-7+-6+-5+-4+-3+-2+-1+0+1+2+3+4+5+6+7+8+9+10
=(-9+9)+(-8+8)+(-7+7)+(-6+6)+(-5+5)+(-4+4)+(-3+3)+(-2+2)+(-1+1)+0+10
=0+0+0+0+0+0+0+0+0+0+10
=0+10
=10
Các số tm -10 < x < 11 là : -9;-8;-7;....;-1;0;1;2;3;....;10
Xét A = -9+(-8)+(-7)+....+(-1)+0+1+2+3+...+10
= (-9+9)+(-8+8)+.....+(-1+1)+0+10
= 0+0+....+0+10 = 10
Vậy ..............
Tk mk nha
Vì \(x\in Z\) và - 10 < x < 11
=> \(x\in\) { - 9 ; - 8 ; - 7 ; .... ; - 1 ; 0 ; 1 ; ...... ; 10 }
Tổng của tất cả các số nguyên x là :
( - 9 ) + ( - 8 ) + ...... + ( - 1 ) + 0 + 1 + 2 + 3 + ..... + 10
= [ ( - 9 ) + 9 ] + [ ( - 8 ) + 8 ] + .......+ [ ( - 1 ) + 1 ] + 0 + 10
= 0 + 0 + .......... + 0 + 0 + 10
= 10
Vậy tổng tất cả các số nguyên x thoản mãn là 10.